Pola Komunikasi Organisasi Iksass Dalam Kaderisasi Santri Baru - Shofwan Hadi; Nur Ainiyah (Maddah : Jurnal Komunikasi dan Konseling Islam, 2022)
Humans are social creatures who cannot live alone without the help of other humans, by nature humans always live together. The purpose of this study was to describe the communication pattern of the IKSASS organization in the cadre of new students. The research method used is qualitative research with a case study research model. Based on the results of the study, there are several communication patterns including linear (one-way) patterns, especially during the material delivery session, interactional patterns (two-way) when questions and answers are opened, and transactional patterns (many directions) when the discussion forum takes place, with this communication, new students get a positive message and some teachings such as mutual respect, especially to teachers, adapt quickly in the pesantren environment, have a salafi appearance, and are accompanied by akhlaqul karimah.